1982
DOI: 10.1029/jc087ic07p04981
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variations of minor constituents in the stratosphere modeled as a function of latitude and season

Abstract: Photodissociation and collision processes in the atmosphere cause significant diurnal variations of short‐lived minor constituents, in particular among the group of catalysts HOx, NOx, and ClOx. Results of diurnal variation experiments within the framework of the Oxford zonally averaged model are presented. With 49 collision reactions and 13 photodissociation reactions, the model incorporates the most important processes known at present. The model extends from pole to pole and from the surface to about 60 km … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0
2

Year Published

1984
1984
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 38 publications
5
23
0
2
Order By: Relevance
“…The present study shows that the global view of WACCM on the daily ozone cycle is invaluable for understanding and planning a correction method. Generally, the results of WACCM are in good agreement with previously reported results of photochemical box models at northern midlatitudes (Herman, 1979;Fabian et al, 1982;Pallister and Tuck, 1983). WACCM and the box models show a daily cycle of stratospheric ozone with a 1 % decrease after sunrise and a slow ascent to approximately 3-5 % in the late afternoon (similar to Fig.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The present study shows that the global view of WACCM on the daily ozone cycle is invaluable for understanding and planning a correction method. Generally, the results of WACCM are in good agreement with previously reported results of photochemical box models at northern midlatitudes (Herman, 1979;Fabian et al, 1982;Pallister and Tuck, 1983). WACCM and the box models show a daily cycle of stratospheric ozone with a 1 % decrease after sunrise and a slow ascent to approximately 3-5 % in the late afternoon (similar to Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Pallister and Tuck (1983) modelled the diurnal ozone cycle at 34 • N with a photochemical box model and confirmed the results of Herman (1979). Furthermore, Fabian et al (1982) indicated latitudinal and seasonal effects by utilisation of a two-dimensional, zonally averaged model. At that time the model utilised by Fabian et al (1982) did not couple dynamics and diurnal photochemistry.…”
Section: Introductionsupporting
confidence: 49%
See 3 more Smart Citations